Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(2 + 4 + 6 + 8 + ... + 2014) - (3 + 5 + 7 + 9 + ... + 2011)
= 2 + 4 + 6 + 8 + ... + 2014 - 3 - 5 - 7 - 9 - ... - 2011
= 2 + (4 - 3) + (6 - 5) + (8 - 7) + ... + (2012 - 2011) + 2014 (có 1005 cặp)
= 2 + 2014 + 1 + 1 + ... + 1 (có 1005 số 1)
= 2016 + 1005
= 3021
(2+4+6+8+...+2014)-(3+5+7+9+...+2011)
= 2+4+6+8+..+2014-3-5-7-9-...-2011
= (2-3)+(4-5)+(6-7)+(8-9)+...+(2010-2011)+2011+2012+2013+2014
= (-1)+(-1)+(-1)+(-1)+...+(-1)+2011+2012+2013+2014 gồm [(2011-2):1+1]:2=1005 số -1
=(-1).1005+2011+2012+2013+2014
=-1005+2011+2012+2013+2014
=7045
a, không có x :v
b, (2x + 1)3 = 729
=> (2x + 1)3 = 93
=> 2x + 1 = 9
=> 2x = 8
=> x = 4
vậy_
c, 97 : x = 97
=> x = 97 : 97
=> x = 1
vậy_
d, x5 : 83 = 64
=> x5 : 83 = 82
=> x5 = 82.83
=> x5 = 85
=> x = 8
vậy_
a) 3x : 3 = 81
3x = 27 = 33
=> x = 3
b) (2x+1)3 = 729 = 93
=> 2x + 1 = 9
2x = 8
x = 4
c) 97: x = 97
x = 1
d) x5 : 83 = 64 = 82
x5 = 83.82 = 85
=> x = 8
a) 3/8 . x = 9/8 - 1
3/8 . x = 1/8
x = 1/8 : 3/8
x = 1/3
b) 4/5 . x = 7/5 - 1/5
4/5 . x = 6/5
x = 6/5 : 4/5
x = 3/2
c) 12/7 : x + 2/3 = 7/5
12/7 : x = 7/5 - 2/3
12/7 : x = 11/15
x = 12/7 : 11/15
x = 180/77
d) 3.(x + 7) - 15 = 27
3.(x + 7) = 27 + 15
3.(x + 7) = 42
x + 7 = 42 : 3
x + 7 = 14
x = 14 - 7
x = 7
a) \(\dfrac{3}{8}x=\dfrac{9}{8}-1\)
\(\Rightarrow\dfrac{3}{8}x=\dfrac{1}{8}\)
\(\Rightarrow x=\dfrac{1}{8}:\dfrac{3}{8}=\dfrac{1}{3}\)
b) \(\dfrac{4}{5}x=\dfrac{7}{5}-\dfrac{1}{5}\)
\(\Rightarrow\dfrac{4}{5}x=\dfrac{6}{5}\)
\(\Rightarrow x=\dfrac{6}{5}:\dfrac{4}{5}=\dfrac{3}{2}\)
c) \(\dfrac{12}{7}:x+\dfrac{2}{3}=\dfrac{7}{5}\)
\(\Rightarrow\dfrac{12}{7}:x=\dfrac{7}{5}-\dfrac{2}{3}\)
\(\Rightarrow\dfrac{12}{7}:x=\dfrac{11}{15}\)
\(\Rightarrow x=\dfrac{12}{7}:\dfrac{11}{15}=\dfrac{180}{77}\)
d) \(3\left(x+7\right)-15=27\)
\(\Leftrightarrow3\left(x+7\right)=42\)
\(\Leftrightarrow x+7=14\Leftrightarrow x=7\)
\(\frac{9}{8}-\frac{-11}{8}=\frac{9-\left(-11\right)}{8}=\frac{9+11}{8}=\frac{20}{8}=\frac{5}{2}\)
\(-\frac{1}{2}-\frac{5}{2}=\frac{-1-5}{2}=\frac{-6}{2}=-3\)
\(\frac{4}{3}-\frac{7}{3}=\frac{4-7}{3}=\frac{11}{3}\)
\(\frac{3}{-5}-\frac{-8}{10}=\frac{6}{-10}-\frac{-8}{10}=\frac{-6}{10}-\frac{-8}{10}=\frac{-6-\left(-8\right)}{10}=\frac{-6+8}{10}=\frac{2}{10}=\frac{1}{5}\)
\(\frac{5}{7}-\frac{-3}{21}=\frac{5}{7}-\frac{-1}{7}=\frac{5-\left(-1\right)}{7}=\frac{5+1}{7}=\frac{6}{7}\)
\(\frac{4}{-3}-\frac{9}{27}=\frac{4}{-3}-\frac{1}{3}=\frac{-4}{3}-\frac{1}{3}=\frac{-4-1}{3}=\frac{-5}{3}\)
\(\frac{7}{29}-\frac{9}{29}=\frac{7-9}{29}=\frac{2}{29}\)
\(\frac{-7}{22}-\frac{9}{22}=\frac{-7-9}{22}=\frac{-16}{22}=\frac{-8}{11}\)
\(\frac{-23}{7}-\frac{31}{7}=\frac{-23-31}{7}=\frac{-54}{7}\)
Lời giải:
$\frac{3}{7}+\frac{-8}{9}+\frac{-7}{8}$
$=\frac{3}{7}-\frac{7}{8}-\frac{8}{9}$
$=\frac{216}{504}-\frac{441}{504}-\frac{448}{504}$
$=\frac{-673}{504}$